Characterization of Streptomyces Isolates Associated with Estuarine Fish Chanos chanos and Profiling of Their Antibacterial Metabolites-Crude-Extract - Muhammad A. Kurnianto; Harsi D. Kusumaningrum; Hanifah N. Lioe (International Journal of Microbiology)
Streptomyces has been reported as an essential producer of bioactive substances, including antibiotics and other types of antimicrobials. This study investigated antibacterial-producing Streptomyces isolated from the gut of estuarine fish Chanos chanos, emphasizing screening for the producer of peptide-containing antibacterial compounds. Eighteen isolates were found during preliminary screening, in which four isolates showed the best antibacterial activities. Based on the morphological, physiological, and biochemical characterization, as well as 16S rRNA partial sequencing, all of the four isolates belonged to Streptomyces. Three isolates were suspected as novel isolate candidates based on homology presentations and phylogenetic tree analysis. Disk-diffusion assay of the metabolite-crude-extract from the isolates showed broad-spectrum inhibitory activities against Staphylococcus aureus ATCC 25923, Bacillus cereus ATCC 10876, Escherichia coli ATCC 25922, and Pseudomonas aeruginosa InaCC B52 with minimum inhibitory concentration and minimum bactericidal concentration ranging from 2.5–10 mg/mL and 5–10 mg/mL, respectively. The highest antibacterial activity with low MIC and MBC values was shown by isolate AIA-10. Qualitative HPLC profiling revealed that the metabolic-crude-extracts showed many peaks with intensive area at 210 and 214 nm, especially from SCA-11 and AIA-10, indicating the presence of peptide groups in the structure of the constituent compound. The results also suggested that crude extracts SCA-11 and AIA-10 had higher hydrophobicity properties than the other extracts. Further characterization of the active compound was needed to find out which compounds were responsible for the antibacterial activity. The results of this study indicated that some Streptomyces isolated from new environmental niches, i.e., gut of estuarine fish Chanos chanos, produce promising peptide-containing bioactive compounds.